2021
DOI: 10.18410/jebmh/2021/249
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Spectrum of Central Nervous System Lesions in a Tertiary Care Hospital in Eastern India

Abstract: BACKGROUND Tumours of central nervous system (CNS) are reported to be less than 2 % of all malignancies. In India, CNS tumours constitute about 1.9 % of all tumours. The CNS space occupying lesions cause grave life-threatening outcomes irrespective of their nature as they grow in a confined space and are present close to vital structures. Hence, it is of great importance to establish the accurate diagnosis for proper and timely neurosurgical intervention. METHODS This was a retrospective study carried out in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Out of the 160 CNS lesions, neoplastic outnumbered the non-neoplastic lesions. Other studies in India conducted by Khonglah et al and Naik et al showed 86.13% versus 13.87% and 91% versus 9% distribution of lesions of neoplastic versus non-neoplastic pathology, respectively [ 2 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 160 CNS lesions, neoplastic outnumbered the non-neoplastic lesions. Other studies in India conducted by Khonglah et al and Naik et al showed 86.13% versus 13.87% and 91% versus 9% distribution of lesions of neoplastic versus non-neoplastic pathology, respectively [ 2 , 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, astrocytoma was the most common tumor followed by meningioma, a finding in concordance with those of Khonglah et al, Agarwal et al, and Aryal [ 2 , 5 , 9 ]. However, various studies across India have reported meningioma to be the commonest tumor followed by astrocytoma [ 6 , 7 ]. Other frequently diagnosed tumors in our study were pituitary adenoma, schwannoma, and oligodendroglioma.…”
Section: Discussionmentioning
confidence: 99%